Clinical comparison of whitening efficacy and tooth sensitivity of different concentrations of hydrogen peroxide photoactivated with violet or blue LEDs - Oliveira, Maria Gabriela Veiga Vidal de (2024)
Abstract: This study evaluated the photoactivation of hydrogen peroxide gels at different concentrations using blue or violet LED in terms of whitening efficacy and tooth sensitivity. Forty patients were randomly divided into 4 groups: HP6V (violet LED and 6% hydrogen peroxide), HP6B (blue LED and 6% hydrogen peroxide), HP35V (violet LED and 35% hydrogen peroxide), and HP35B (blue LED and 35% hydrogen peroxide). The L*, a* and b* values were measured before, 1 week and 3 months after treatment, and the ΔE and ΔWID values were calculated. Tooth sensitivity was measured using a visual analogue scale (VAS) before, immediately after, and 24 h after bleaching. The ΔE, ΔWID and bleaching sensitivity values were subjected to the ANOVA test and Bonferroni post-test. HP35V and HP35B showed higher whitening efficacy than HP6VL, while HP6V did not show statistical differences compared to the other groups. Regarding bleaching-related sensitivity, the HP6V and HP6B groups presented the lowest values when compared to HP35V and HP35B. HP6V showed whitening efficacy comparable to HP35V and HP35B but with reduced tooth sensitivity. Trial registration number: NCT06165458; registration date: 12/09/2023.